PENINGKATAN PERAN IBU RUMAH TANGGA TERHADAP PENCEGAHAN SINDROMA METABOLIK - Nazwirman Nazwirman; Juniarti Juniarti; Yurika Sandra (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2019)
Obesity is a health problem throughout the world. Obesity as a component of the metabolic syndrome, is very complex and multifactorial. Obesity is generally caused by energy input exceeding the body's use of energy for the sake of basal metabolism, physical activity, food waste disposal and for growth. The city of Tangerang ranks first for the prevalence of obesity from Banten Province. The results of the activity stated that the prevalence of obesity in Taklim women was 44 percent. This program is an empowerment of Majelis Taklim women to overcome and prevent health problems, especially metabolic syndrome by conducting screening and counseling. The result is that participants can know the symptoms and signs of metabolic syndrome through anthropometric measurements and laboratory tests, participants can know how to prevent metabolic syndrome and can provide explanations to the family and the surrounding community about prevention of metabolic syndrome